2006
DOI: 10.1111/j.1525-1470.2006.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

What is Standard of Care in the Evaluation of Elastosis Perforans Serpiginosa? A Survey of Pediatric Dermatologists

Abstract: Elastosis perforans serpiginosa is a rare chronic dermatosis characterized by extrusion of altered elastic fibers through the epidermis. It often occurs in association with a variety of connective tissue disorders, and may develop following penicillamine therapy; however, it may also present without comorbidities. There are currently no well-established protocols for the investigation of possible associated disorders in patients who present with elastosis perforans serpiginosa. We describe three patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…1 Esta entidade tem sido tradicionalmente classificada, por ordem decrescente de frequência, como idiopática -a maioria dos casos, reativa -cerca de 25 -40%, ou excecionalmente fármaco-induzida. [3][4][5] Entre os casos idiopáticos tem sido descrita associação familiar, com formas hereditárias autossómicas dominantes ou recessivas. 5 A forma reativa pode ocorrer associada a síndrome de Down, síndrome de Marfan, síndrome de Rothmund-Thomson, doença de Ehlers-Danlos, acrogeria, pseudoxantoma elástico, osteogénese imperfeita, ou esclerodermia.…”
Section: Introduçâounclassified
See 1 more Smart Citation
“…1 Esta entidade tem sido tradicionalmente classificada, por ordem decrescente de frequência, como idiopática -a maioria dos casos, reativa -cerca de 25 -40%, ou excecionalmente fármaco-induzida. [3][4][5] Entre os casos idiopáticos tem sido descrita associação familiar, com formas hereditárias autossómicas dominantes ou recessivas. 5 A forma reativa pode ocorrer associada a síndrome de Down, síndrome de Marfan, síndrome de Rothmund-Thomson, doença de Ehlers-Danlos, acrogeria, pseudoxantoma elástico, osteogénese imperfeita, ou esclerodermia.…”
Section: Introduçâounclassified
“…1 Esta entidade tem sido tradicionalmente classificada, por ordem decrescente de frequência, como idiopática -a maioria dos casos, reativa -cerca de 25 -40%, ou excecionalmente fármaco-induzida. [3][4][5] Entre os casos idiopáticos tem sido descrita associação familiar, com formas hereditárias autossómicas dominantes ou recessivas.…”
unclassified
“…The lesions are characteristically symmetrical except in cases associated with Down's syndrome or D-penicillamine treatment. 7 Disseminated lesions, albeit rare, have been described. [13][14][15] The condition most commonly affects the face, the neck and the upper limbs.…”
Section: Discussionmentioning
confidence: 99%
“…2 Familial groupings have been reported with varying hereditary patterns. 7 Although the etiopathogenesis is as yet unclear, it is believed that the focal inflammation in the dermis, which has a biochemical or mechanical origin, may induce the formation of epidermal and follicular channels to expulse abnormal elastic fibers considered irritants. Fujimoto et al reported interactions between elastin peptides and their 67kDa receptors expressed in the epidermis surrounding the transepidermal elimination channel, which may participate in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 The disease is associated with systemic disorders like Down syndrome, EhlersDanlos syndrome, Marfan syndrome 2,3 and it also exists in a drug-induced form by pencillamine. 4 EPS is characterized by increased elastic tissue in papillary dermis, inflammation and transepidermal elimination of abnormal elastic fibers.…”
Section: Introductionmentioning
confidence: 99%